Natural rubber/graphene oxide composites: Effect of sheet size on mechanical properties and strain-induced crystallization behavior - X. Wu; T. F. Lin; Z. H. Tang; B. C. Guo; G. S. Huang (eXPRESS Polymer Letters, 2015)
In order to analyze the influence of the lateral size of graphene oxide (GO) on the properties of natural rubber/graphene oxide (NR/GO) nanocomposites, three different sized graphene oxide sheets, namely G1, G2 and G3 were used to fabricate a series of NR/GO nanocomposites by latex mixing. The results indicate that adding GO can remarkably increase the modulus of NR. The enhancement of modulus is strongly dependent on the size of GO sheets incorporated. G1 with smallest sheet size gives the maximum reinforcement effect compared with G2 and G3. Dynamic mechanical measurement and swelling ratios (Qf/Qg) indicate that G1 has stronger interfacial interaction with NR. XRD shows G1 is more effective in accelerating the strain-induced crystallization (SIC) of NR. The strong interfacial interaction facilitates the stress transfer and strain-induced crystallization, both of which lead to the improved modulus.